Exploring chronic pain related attentional experiences, distress and coping strategies among Arabic-speaking individuals in Jordan and the United Kingdom - Abudoush, Ahmad N.; Ali, Khalifa; Kiran, Tayyeba; Panagioti, Maria; Poliakoff, Ellen; Mo Hom, Nang; Husain, Nusrat (Frontiers in Psychology, 2023)
Introduction The lived experiences of chronic pain (CP) among Arabic-speaking populations remain underexplored. A better understanding of these experiences and their associations with attention difficulties, coping mechanisms, and treatment options could lead to improved support for this group. Methods This qualitative study utilised a descriptive design and involved one-to-one interviews with 51 participants with CP who had just completed two attention tasks. Interviews were conducted using a semi-structured topic guide, transcribed verbatim and translated from Arabic to English before agreeing on the coding framework. Themes and subthemes were extracted using a framework analysis approach. Results The study identified six main themes: Factors contributing towards developing or exacerbating CP, the impact of CP on psychosocial functions, including attention, the perceived role of social support, coping strategies for managing CP, perceptions about available treatments and recommendations for interventions. Discussion CP significantly impacts individuals’ physical and psychosocial functions, and it is reciprocally associated with attentional difficulties. Despite using various approaches to manage their CP, none of the participants used psychological interventions or counselling. Understanding the diverse impacts of CP and the coping strategies employed to develop culturally sensitive interventions, review current related policies, and improve healthcare services is crucial to managing CP among this population.